Identification and elimination of an immunodominant T-cell epitope in recombinant immunotoxins based on Pseudomonas exotoxin A - Mazor, Ronit; Vassall, Aaron N.; Eberle, Jaime A.; Beers, Richard; Weldon, John E.; Venzon, David J.; Tsang, Kwong Y.; Benhar, Itai; Pastan, Ira (Proceedings of the National Academy of Sciences - PNAS, 2012)
Recombinant immunotoxins (RITs) are chimeric proteins that are being developed for cancer treatment. We have produced RITs that contain PE38, a portion of the bacterial protein Pseudomonas exotoxin A. Because the toxin is bacterial, it often induces neutralizing antibodies, which limit the number of treatment cycles and the effectiveness of the therapy. Because T cells are essential for antibody responses to proteins, we adopted an assay to map the CD4 ⁺ T-cell epitopes in PE38. We incubated peripheral blood mononuclear cells with an immunotoxin to stimulate T-cell expansion, followed by exposure to overlapping peptide fragments of PE38 and an IL-2 ELISpot assay to measure responses. Our observation of T-cell responses in 50 of 50 individuals correlates with the frequency of antibody formation in patients with normal immune systems. We found a single, highly immunodominant epitope in 46% (23/50) of the donors. The immunodominant epitope is DRB1-restricted and was observed in subjects with different HLA alleles, indicating promiscuity. We identified two amino acids that, when deleted or mutated to alanine, eliminated the immunodominant epitope, and we used this information to construct mutant RITs that are highly cytotoxic and do not stimulate T-cell responses in many donors.